INCONSISTENCY OF PRISON CRIMINAL SANCTIONS FOR CHILDREN AND CRIMINAL OBJECTIVES IN RKUHP - Triwati, Ani (Walisongo Law Review (Walrev), 2019)
Children are vulnerable groups when dealing with the criminal justice system based on various analyzes. Therefore a special mechanism is needed to protect the interests of children facing the law. It is affirmed in the UN Regulations for the Protection of Children Who Lost their Freedom that the child court system must uphold rights and safety and promote the physical and mental well-being of children. Prison sentences must be used as a last resort. Children who are in conflict with the law, will get a label or stigmatization from the community from the moment the case processes at the police level until the court ruling is even possible forever. This article will discuss the implications of inconsistencies in prison sanctions for children and the purpose of criminal prosecution in RKHUP, that children who proceed in criminal justice, the label will be inherent indefinitely, so it is likely that children tend to commit criminal acts again. Prison sentences will bring children to learn more about their environment.